Implementation of Al-Ijarah Al-Maushufah Fi Al-Dzimmah Acad at Indonesian Sharia Bank - Sahrani, Sahrani; Adha, Sitti Nurul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
This study aims to determine the inhibiting factors for the implementation of the Ijarah Maushufah Fi Dzimmah contract in Islamic banks, especially in the city of Makassar. This study uses a literature study research method, with research data collected through books, articles, journals, and interviews and then analyzed by descriptive methods. A descriptive method is used to describe and explain the opinions of fiqh scholars about the Ijarah Maushufah Fi Dzimmah contract in Islamic law, as well as describe the results of the analysis of Islamic banking records and documents to determine the inhibiting factors for the implementation of the Maushufah Fi Dzimmah ijarah contract at the Makassar City Sharia Bank by conducting personal interviews. with banking practitioners in the marketing division of financing at Bank BNI Syariah, Bank BTN Syariah, and Bank Muamalat. The results showed that the inhibiting factors for the implementation of the Maushufah Fi Dzimmah contract include: (1) the absence of standard regulations from the government (OJK and BI) regarding the implementation of the Maushufah Fi Dzimmah contract; and (2) the methods of implementing the product development process and system transformation that have been implemented run by Islamic banks is still difficult; (3) lack of knowledge of Islamic bank practitioners on Al-Ijarah Al-Maushufah Fi Dzimmah contracts; (4) Islamic banking financing is dominated by murabahah contracts; and (5) low public interest in Ijarah-based products.